2017
DOI: 10.1159/000458529
|View full text |Cite
|
Sign up to set email alerts
|

c-Rel Promotes Invasion of Choriocarcinoma Cells via PI3K/AKT Signaling

Abstract: Objective: Choriocarcinoma is the most common epithelial cancer among gestational trophoblastic diseases (GTDs); the mechanism of trophoblastic carcinogenesis is unknown. This study aimed to examine the expression of NF-κB family proteins in GTDs and placental tissues as well as the roles of c-Rel in choriocarcinoma. Methods: We examined the expression of NF-κB family proteins in normal placenta and hydatidiform mole tissues as well as extravillous trophoblast (EVT) and choriocarcinoma cell lines by Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, GTD is also been characterized by abnormal proliferation and apoptosis 13,14 and associated with signal pathway regulation. Sekiya found that c‐Rel might play a role in promoting the invasion of choriocarcinoma cells through PI3K/AKT signalling 15 . miR‐30a‐5p which we studied in this article may play an important role in the regulation of ERK signalling 16 …”
Section: Introductionmentioning
confidence: 85%
“…In addition, GTD is also been characterized by abnormal proliferation and apoptosis 13,14 and associated with signal pathway regulation. Sekiya found that c‐Rel might play a role in promoting the invasion of choriocarcinoma cells through PI3K/AKT signalling 15 . miR‐30a‐5p which we studied in this article may play an important role in the regulation of ERK signalling 16 …”
Section: Introductionmentioning
confidence: 85%
“…The activation of PI3K/AKT signaling pathway had been verified in numerous cancers, including choriocarcinoma, which was involved in the modulation of cell survival, proliferation, differentiation, and migration. 27,28 5-Fu can inactivate PI3K/AKT signaling pathway in many cancer cells. 29 Zhang et al 30 proved that downregulation of USP22 potentiated the chemosensitivity of hepatocellular carcinoma cells to 5-Fu by inactivating AKT.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB subunit c-Rel plays an important role in initiation of inflammatory responses, but also functions as a transcriptional repressor of inflammatory genes [45]. NF-κB subunit c-Rel expresses in villi of normal placenta, and plays a key role in enhancing the invasion of choriocarcinoma cells through phosphatidylinositol-3-OH kinase-Akt signaling [46]. Low levels of NF-κB subunits c-Rel, p50, and p105 in myometrium are favorable for pregnancy maintenance, but increasing expression of p65, c-Rel, and p50 subunits is associated with the onset of parturition in humans [29].…”
Section: Discussionmentioning
confidence: 99%